Development of TaqMan real-time RT-PCR for detection of avian reoviruses - Guo, Kejun; Dormitorio, Teresa V.; Ou, Shan-Chia; Giambrone, Joseph J. (Journal of virological methods, 2011)
► Avian reoviruses (ARVs) are cause of economic losses in poultry. ► A TaqMan real-time RT-PCR assay for detection of ARVs was developed. ► This test was rapid, specific, and sensitive and will be useful in diagnostic laboratories and for all the quantitation of vaccine viruses for pharmaceutical companies. Avian reoviruses (ARVs) are an important cause of economic losses in commercial poultry. A TaqMan real-time RT-PCR assay for detecting of ARVs was developed. The primer-probe set was from the conserved region of ARV S4 genome segment. Real-time RT-PCR detected ARV strains including CO8 and ss412 strains, which belonged to different serological subgroups, and the test had no cross-reaction with other avian viruses. The detection limit of this assay was 5 ARV genome copies per 5μl and was 150 times more sensitive than traditional RT-PCR. Statistical analyses indicated excellent reproducibility. For ARV strain 2408, a titer of 50% embryo infection dose and 50% tissue culture infectious dose equivalent to 3.9±0.8, and 2.9±0.3 ARV genome copies, respectively. This test was rapid, specific, and sensitive for the detection of ARVs and will be useful in veterinary diagnostic laboratories and for the quantitation of vaccine viruses for pharmaceutical companies.